Weddellian marine/coastal vertebrates diversity from a basal horizon (Ypresian, Eocene) of the Cucullaea I Allomember, La Meseta formation, Seymour (Marambio) Island, Antarctica - Reguero, Marcelo A. (2012)
The La Meseta Formation crops out in Seymour/Marambio Island, Weddell Sea, northeast of the Antarctic Peninsula and contains one of the world's most diverse assemblages of Weddellian marine/coastal verte-brates of Early Eocene (Ypresian) age. The La Meseta Formation is composed of poorly consolidated, marine sandstones and siltstones which were deposited in a coastal, deltaic and/or estuarine environment. It includes marine invertebrates and vertebrates as well as terrestrial vertebrates and plants. The highly fossiliferous basal horizon (Cucullaeashell bed, Telm 4 of Sadler 1988) of the CucullaeaI Allomember is a laterally extensive shell bed with sandy matrix. The fish remains, including 35 species from 26 families, of the Ypresian Cucullaeabed represent one of the most abundant and diverse fossil vertebrate faunas yet recorded in southern latitudes. Stratigraphic distribution and phylogenetic relationships of the Weddellian sphenisciforms are consistent with a first radiation of this group in the Early Eocene. The first inquestionable archaeocete from Antarctica is recorded in this unit and is referred to a new taxon.